Effect of Theobroma cacao L. on the Efficacy and Toxicity of Doxorubicin in Mice Bearing Ehrlich Ascites Carcinoma - Priyanka P. Patil; Pukar Khanal; Vishal S. Patil; Rajitha Charla; Darasaguppe R. Harish; Basanagouda M. Patil; Subarna Roy (MDPI AG, 2022)
Background and objective: Doxorubicin is a widely used chemotherapeutic agent that causes oxidative stress leading to cardiotoxicity, hepatotoxicity, and nephrotoxicity. In contrast, Theobroma cacao L. has been recorded as an anticancer agent and found to be protective against multiple chemical-induced organ injuries, including heart, liver, and kidney injuries. The present study investigated the possible role of extracts from T. cacao beans for organ-protective effects in doxorubicin-induced toxicity in mice bearing Ehrlich ascites carcinoma (EAC). Methodology: After survival analysis in rodents, cocoa bean extract (COE) was investigated for its efficacy against EAC-induced carcinoma and its organ-protective effect against doxorubicin-treated mice with EAC-induced carcinoma. Results: Significant reductions in EAC and doxorubicin-induced alterations were observed in mice administered the COE, either alone or in combination with doxorubicin. Furthermore, COE treatment significantly increased the mouse survival time, life span percentage, and antioxidant defense system. It also significantly improved cardiac, hepatic, and renal function biomarkers and markers for oxidative stress, and it also reduced doxorubicin-induced histopathological changes. Conclusion: COE acted against doxorubicin-induced organ toxicity; potent antioxidant and anticancer activities were also reflected by the COE itself. The COE may therefore serve as an adjuvant nutraceutical in cancer chemotherapy.